Experimental and numerical studies on scaling and thermal conductivity of backward step ethanol fueled micro-combustor - Vinay Sankar; Ratna Kishore Velamati; Sudipto Mukhopadhyay (Case Studies in Thermal Engineering)
An experimental study was performed to explore the flammability limits of ethanol fuelled stepped micro-combustor (three-step) at different scales (by changing surface area to volume ratio (S/V)). The combustors were made of quartz, stainless steel, and aluminium, each with a thermal conductivity that differed by order of magnitude. The study indicates that reducing the S/V, leads to upstream flame stabilization, with aluminium combustors having superior flame stabilization nearer to the combustor inlet followed by stainless steel and quartz combustors. It was observed that for all scales of combustors, better blowout limit and flashback limit were observed at ϕ=1.1. Interestingly the blowout limit followed a trend similar to that of laminar burning velocity (SL) and the flashback limit followed a trend similar to temperature dependency (α) of SL with ϕ. The aluminium combustors at all scales showed better outer wall mean temperature (Tmean) and uniformity (σT), making it more suitable for Thermoelectric Generator (TEG) applications. The uniform wall temperature distribution in the aluminium combustor allows for the mounting of more TEG modules compared to Stainless steel combustors, where TEG modules can only be effectively mounted on the second and third steps due to non-uniform wall temperatures in the first step.